Endoscopic papillectomy for carcinoma of the ampulla of Vater: Possible standardization based on endoscopy and immunohistochemistry - Yoshihiro, Hamada; Kensei, Maeshiro; Yoshifuku, Nakayama (Turkish Journal of Gastroenterology, 2014)
Abstract Background/Aims: Clinicopathological investigation of the indications for the use of endoscopic papillectomy as a treatment for carcinoma in situ of the ampulla of Vater (CAV). Materials and Methods: Of 97 patients diagnosed with CAV in our department over the last 15 years, the 5 patients who received a carcinoma in situ diagnosis and were included in this retrospective study. Results: The lesions in the patients were classified as either the superficial or luminal type, based on endoscopic findings. Histological findings showed that the major duodenal papilla (Ad) was the main site of CAV in the superficial type and that the common duct into the duodenal lumen (Ac) was the primary site in the luminal type. Immunohistochemical staining showed that the superficial-type lesions were positive for cytokeratin 20, suggesting development of the cancer from the Ad. The luminal-type lesion was positive for cytokeratin 7 and negative for cytokeratin 20, suggesting an origin in the pancreatobiliary duct. Mucin-2 was expressed in the superficial type, and mucin-1 in the luminal type. Conclusion: Superficial-type lesions, which are principally located in the Ad, exhibit little tendency to invade surrounding tissues, whereas the luminal-type lesions, which are predominantly located in the Ac, may tend to be more invasive. Although endoscopic papillectomy might be indicated for the superficial-type lesions, caution is needed in the determination of the extent of luminal-type lesions.